1990
DOI: 10.1017/s0007485300050434
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of organophosphate and carbamate resistance in Culex quinquefasciatus (Diptera: Culicidae) from Cuba

Abstract: Two field-collected strains of Culex quinquefasciatus Say, collected 50 km apart in Havana City, Cuba, were both resistant to malathion and propoxur, while one population also showed low level resistance to temephos. Laboratory selection of the latter population with malathion for 22 generations increased the malathion resistance 1050-fold, temephos resistance 24-fold and propoxur resistance 453-fold compared to the standard laboratory susceptible strain. Synergist studies and biochemical tests indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 8 publications
4
37
1
2
Order By: Relevance
“…Quantitative changes in esterases are common in Culex species. The most frequently observed organophosphateselected resistance mechanism in the common house mosquito C. quinquefasciatus is the amplification of nonspecific esterases Bisset et al 1990;Karunaratne et al 1993) which is similar to the present investigation. These esterases confer insecticide resistance by rapid binding and slow turnover (i.e., sequestration), thus, preventing the organophosphate insecticide from reaching its target site, acetylcholinesterase (Karunaratne et al 1995;Devonshire and Moores 1982).…”
Section: Resultssupporting
confidence: 88%
“…Quantitative changes in esterases are common in Culex species. The most frequently observed organophosphateselected resistance mechanism in the common house mosquito C. quinquefasciatus is the amplification of nonspecific esterases Bisset et al 1990;Karunaratne et al 1993) which is similar to the present investigation. These esterases confer insecticide resistance by rapid binding and slow turnover (i.e., sequestration), thus, preventing the organophosphate insecticide from reaching its target site, acetylcholinesterase (Karunaratne et al 1995;Devonshire and Moores 1982).…”
Section: Resultssupporting
confidence: 88%
“…These low values of esterase activity increments and the RR at maximum 11.2-fold agree with previously reported data (Villani et al 1983, Breeden et al 1984, Brown 1986, Bisset et al 1990) that indicated a low elevation of esterase activity may be responsible for the establishment of low levels of resistance to a variety of organophosphates. The significant increase in a esterase activity with the concomitant decrease of the b esterase, suggest a selection for a esterases as a biochemical mechanism for insecticide resistance.…”
Section: Discussionsupporting
confidence: 92%
“…The most frequently observed organophosphate-selected resistance mechanism in the common house mosquito Culex quinquefasciatus is the amplification of non-specific esterases [1][2][3]. These esterases confer insecticide resistance by rapid binding and slow turnover (i.e.…”
Section: Introductionmentioning
confidence: 99%